2005
DOI: 10.1308/003588405x71018
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the construction of cancer guidelines demonstrated by the analyses of colorectal referrals

Abstract: INTRODUCTION The aim of this study was to develop a system to compare and validate cancer referral guidelines, identifying the pitfalls in their development and provide a mechanism to evaluate their efficacy.PATIENTS AND METHODS 3302 patients referred from primary care with colorectal symptoms over a 3-year period were assessed. All participants had a comprehensive history obtained via a questionnaire that incorporated all colorectal symptoms. The questionnaires were completed prior to assessment at the hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
0
25
1
Order By: Relevance
“…In the case of the FAST Score, its greatest advantage is simplicity and it could be calculated automatically by laboratory information management systems (LIMS) widely used to report results in laboratory medicine, with or without appropriate interpretative comments added by the LIMS, or through simple calculators developed for the Internet or as easy to download apps, since age and sex are generally available in health care systems and, if not, are easily collected from patients with symptoms prior to referral for colonoscopy along with the f‐Hb. We think the simplicity of this prediction model may encourage the implementation of the FAST Score in comparison with previous developed prediction models for CRC detection that are based on several clinical and analytical variables which must be collected from disparate sources before the model is applied,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the FAST Score, its greatest advantage is simplicity and it could be calculated automatically by laboratory information management systems (LIMS) widely used to report results in laboratory medicine, with or without appropriate interpretative comments added by the LIMS, or through simple calculators developed for the Internet or as easy to download apps, since age and sex are generally available in health care systems and, if not, are easily collected from patients with symptoms prior to referral for colonoscopy along with the f‐Hb. We think the simplicity of this prediction model may encourage the implementation of the FAST Score in comparison with previous developed prediction models for CRC detection that are based on several clinical and analytical variables which must be collected from disparate sources before the model is applied,…”
Section: Discussionmentioning
confidence: 99%
“…These prediction models, systematically reviewed in detail recently, are calculated from mathematical equations based mainly on symptoms, although information regarding demographics, other variables and results of investigations are sometimes also included . Although their diagnostic accuracy is generally deemed to be satisfactory and better than the existing referral criteria, these prediction models have not been widely implemented, in part due to their complexity and the difficulty of collection of all of the spectrum of variables required …”
mentioning
confidence: 99%
“…The PCQ and WNS process provides a system with a higher sensitivity and specificity for CRC detection than the current referral guidelines. This is attributed to the benefit of objectively assessing the added risk of cancer when multiple colorectal symptoms co‐exist [6,14]. Furthermore, in the group of patients who score highly a significant proportion are likely to have serious benign conditions such as colitis and polyps (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent national audits and publications have highlighted problems with their efficacy [4][5][6][7][8][9][10][11]. Poor compliance with the referral guidelines by general practitioners (GP), lack of specificity and overwhelming referrals from primary care have all been identified as common causes of a reduction in the efficiency of the referral process.…”
Section: Introductionmentioning
confidence: 99%
“…At this cut-off point, the population urgently referred includes not only patients with cancers but also patients with benign diseases that need urgent management, such as ulcerative colitis and polyps. The use of this questionnaire has been supported by others[18, 47]. An evaluation of the WNS compared with several other tools [13, 15, 23, 35, 40] concluded that the WNS with a threshold of 50 had a comparable sensitivity but a higher specificity than the rest of the tools in detecting cancer, yielding the lowest referral rate.…”
Section: Resultsmentioning
confidence: 73%